Graphene-based Nanocatalysts for Oxygen Reduction and Evolution Reactions in Metal-oxygen Batteries - Kishore, Brij; Singh, Baljeet; Kumar, Surender (Current Catalysis, 2018)
Background: Graphene and its composites with various transition metals and their oxides are widely studied for their applications in electrochemical energy conversion and storage devices. Graphene, a two-dimensional single atomic layer of the carbon atoms, has a high conductivity and high surface area. For these reasons, it has attracted considerable interest in electrochemical devices, such as batteries and supercapacitors. This review aims at identifying these electrocatalysts. Methods: Peer-reviewed research papers were scavenged using various bibliographic databases with graphene as one of the keywords. Research papers with good quality data were screened, analysed and the findings of the papers were summarized using a conceptual framework. Results: All together 80 research articles which have used graphene and/or its nanocomposite are included in the review. These bifunctional electrocatalysts are studied in a metal-oxygen battery which is a hybrid system of a Li-ion battery and a H2-O2 fuel cell. Several metal-oxygen (Zn-O2, Li-O2, Na-O2, K-O2, Ca-O2, Mg-O2, etc.) batteries are known in the literature. Li-O2 battery is another potential device for future electrical vehicles applications with its energy density being about 8 times higher than the state-of-the-art Li-ion battery. Current research works aim to improve the performance of existing metal- oxygen systems and explore the possibilities of using cheaper Na and K as anodes. Two types of reactions occur at the cathode in a metal-oxygen battery and electrocatalysts are employed to improve the kinetics of these reactions for better performance. Conclusion: Several research articles on graphene and its composites with transition metals and their oxides based nanocatalysts claim to improve the oxygen reaction kinetics and cycle life of the batteries. In this review, recent articles of graphene-based nanocatalysts for metal-oxygen batteries are summarized which give the present scenario of research in the field and scope of future work.
Keywords: OER